GUTIERRZ DAN TEOLOGI PEMBEBASAN - Mateus Mali (Jurnal Orientasi Baru, 2016)
Liberation theology emerges as a movement within the Chatolic Church in Latin America in the 1950s and 1960s. This movement is principally as a moral reaction to the poverty and social injustice in the region. Gustavo Guttirrez gives the movement its name: theology of liberation (1971) that attempts to interpret Scripture through the plight of the poor. This essay deals with the Guttirrez concept of theology of liberation. From Gutirrez, we learn that doing theology means to seek to interpret the actions of the Catholic Church and the teachings of Jesus Christ from the perspective of the poor and disadvantaged.